Patch material capable of controllably delivering anti-inflammatory substances as well as preparation method and application of patch material

By using hydrogel-loaded anti-inflammatory substance nanoparticles with adjustable degradation rate in the spinal cord injury area, the controlled delivery and long-term effects of anti-inflammatory substances are achieved, solving the problem of poor effectiveness of existing drug treatments in spinal cord injury and significantly improving the microenvironment of spinal cord contusion.

CN119499218APending Publication Date: 2025-02-25BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311073509.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The inflammatory response caused by spinal cord injury is serious. The existing drug treatment has problems such as low drug utilization, short action time and major side effects, making it difficult to effectively inhibit the inflammatory response in the damaged area.

Method used

The hydrogel-loaded anti-inflammatory substance nanoparticle delivery system with adjustable degradation rate is adopted, combined with electrospinned nanofiber scaffolding, and the controlled delivery and long-term effects of anti-inflammatory substances are achieved through surface modification and gradient density signals.

Benefits of technology

The long-term and stable delivery of anti-inflammatory substances in the injured area is achieved, effectively inhibiting the early inflammatory response of spinal cord contusion, improving the injury microenvironment, and providing favorable conditions for subsequent spinal cord repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499218A_ABST
    Figure CN119499218A_ABST
Patent Text Reader

Abstract

The invention provides a patch material capable of controllably delivering an anti-inflammatory substance, which comprises a polymer fiber layer and a hydrogel layer, and the hydrogel layer is a modified biomacromolecule hydrogel containing anti-inflammatory substance nanoparticles. By adopting the hydrogel-loaded anti-inflammatory nanoparticle delivery system with the adjustable degradation rate, the controllable delivery of anti-inflammatory substances can be realized, and the inflammatory microenvironment in the initial stage of contusion can be effectively regulated and controlled. Meanwhile, the composite patch material can efficiently integrate multiple induction signals such as a topological structure and a gradient density signal, the repair effect is improved, and a new way and a new method are provided for design of spinal cord contusion repair materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomaterials, and in particular relates to a patch material capable of controllably delivering anti-inflammatory substances, a preparation method thereof and an application thereof. Background Art

[0002] Spinal cord injury has a very high disability rate, and clinical manifestations include loss of sensation below the damaged spinal cord segment, motor impairment and sphincter dysfunction, which have a great negative impact on the patient's quality of life and life span. Spinal cord injury has become a global problem that needs to be solved urgently in the medical community. Spinal cord contusion is the most common type of spinal cord injury in clinical practice. The strong inflammatory response in the early stage of injury causes the damage to the injured area to continue to worsen, and the inflammatory area will continue to expand over time, thereby affecting the normal spinal cord tissue. At present, clinically, drug therapy is mainly used to inhibit inflammatory response, but due to the existence of other factors such as the blood-brain barrier, drug therapy has a series of disadvantages such as the short residence time of the drug in the injured area, the short half-life of the drug resulting in limited action time, and low drug utilization rate, and is often accompanied by serious side effects. Therefore, the use of carriers to load anti-inflammatory substances to achieve controlled release and long-term effect at the site of injury has become a good solution to the above problems.

[0003] In the selection of carriers for anti-inflammatory substances, nanoparticles are a good choice. They can prolong the half-life of drugs and anchor the damaged area through surface modification to achieve long-term retention of drugs in the damaged area. Nanoparticles can also pass through the blood-brain-spinal cord barrier to improve the utilization of drugs. However, due to the existence of cerebrospinal fluid circulation, the efficiency of nanoparticles is still limited (Mu J, Du Y, Li X, et al. Collagen-anchored cascade nanoreactors with prolonged intratumoral retention for combined cancer starvation and chemotherapy [J]. Chemical Engineering Journal, 2023, 451: 138554; Householder KT, Dharmaraj S, Sandberg DI, et al. Fate of nanoparticles in the central nervous system after intrathecal injection in healthy mice [J]. Scientific Reports, 2019, 9 (1): 12587.). Summary of the invention

[0004] The present invention provides a patch material for controllable delivery of anti-inflammatory substances. By adopting a hydrogel-loaded anti-inflammatory substance nanoparticle delivery system with adjustable degradation rate, controllable delivery of anti-inflammatory substances can be achieved, effectively regulating the inflammatory microenvironment in the early stage of injury. At the same time, this composite patch material can efficiently integrate multiple induction signals such as topological structure and gradient density signals to improve the repair effect, providing a new approach and method for the design of spinal cord contusion repair materials.

[0005] One of the objects of the present invention is to provide a patch material for controllably delivering anti-inflammatory substances.

[0006] The patch material for controllably delivering anti-inflammatory substances provided by the present invention comprises a polymer fiber layer and a hydrogel layer, wherein the polymer fiber layer is a double-layer polymer fiber layer with growth factor nanoparticles deposited on the surface, and the hydrogel layer is a modified biomacromolecule hydrogel containing anti-inflammatory substance nanoparticles.

[0007] Wherein, the thickness of the polymer fiber layer is 50 to 800 μm, preferably 100 to 500 μm; the thickness of the hydrogel layer is 50 to 800 μm, preferably 100 to 500 μm;

[0008] The inner layer of the polymer fiber layer is a unidirectional orderly arranged polymer fiber layer with growth factor nanoparticles deposited on the surface, and the outer layer is a randomly arranged polymer fiber layer; the polymer in the polymer fiber layer is selected from degradable aliphatic polyesters, preferably at least one selected from polylactic acid, polycaprolactone, polylactic acid-glycolic acid copolymer, polylactic acid-glycolic acid-caprolactone copolymer;

[0009] The growth factor nanoparticles are of a core-shell structure, wherein the shell layer is a bioactive substance and the core layer is a growth factor; the particle size of the growth factor nanoparticles is 30 to 200 nm, preferably 50 to 150 nm; in the growth factor nanoparticles, the bioactive substance simulates the composition of the extracellular matrix, and the bioactive substance is selected from at least one of protein compounds, preferably at least one of collagen, laminin, fibronectin, and collagen; the growth factor has a repair-promoting effect, and the growth factor is selected from at least one of vascular endothelial growth factor, fibroblast growth factor, epidermal growth factor, brain-derived neurotrophic factor, neurotrophic factor-3, glial cell-derived neurotrophic factor, ciliary neurotrophic factor, and nerve growth factor;

[0010] The anti-inflammatory substance nanoparticles comprise a three-layer structure, wherein the inner layer is an anti-inflammatory substance, the middle layer is a cationic polymer, and the outer layer is a polyphenol compound; the particle size of the anti-inflammatory substance nanoparticles is 30 to 200 nm, preferably 50 to 100 nm; in the anti-inflammatory substance nanoparticles, the anti-inflammatory substance is selected from at least one of catalase, superoxide dismutase, interleukin, and reducing molecules (such as curcumin and resveratrol); the cationic polymer is selected from at least one of polyarginine, polylysine, gelatin, polyhistidine, polyethyleneimine, polyacrylamide, and polyacrylamine; and the polyphenol compound is selected from at least one of flavonoids, tannins, phenolic acids, and anthocyanins;

[0011] The modified biomacromolecule is an acrylated biomacromolecule, preferably at least one selected from methacrylated gelatin, methacrylated hyaluronic acid, methacrylated silk fibroin, methacrylated chitosan, and methacrylated sodium alginate.

[0012] The second object of the present invention is to provide a method for preparing the above-mentioned anti-inflammatory patch material, comprising: electrospinning a polymer solution to obtain a double-layer nanofiber membrane with an inner layer of uniaxial orderly arranged nanofibers and an outer layer of randomly arranged nanofibers, then depositing growth factor nanoparticles on the surface of the inner fiber layer by electrostatic spraying, and then mixing a suspension containing anti-inflammatory substance nanoparticles with a modified biomacromolecule solution and a cross-linking agent, spreading it on the surface of the inner fiber layer and cross-linking it under ultraviolet light to obtain the patch material for controllable delivery of anti-inflammatory substances. Preferably, the preparation method specifically comprises the following steps:

[0013] Step (1) electrospinning the polymer solution A to prepare a double-layer polymer fiber layer;

[0014] Step (2) using coaxial electrostatic spraying to spray the growth factor solution B and the bioactive substance solution C onto the inner surface of the double-layer polymer fiber layer to obtain a polymer fiber layer with electrostatically deposited growth factor nanoparticles;

[0015] Step (3) mixing the anti-inflammatory substance solution D with the cationic polymer solution E to obtain a suspension M, and then adding the polyphenol compound solution F to the suspension M to obtain an anti-inflammatory substance nanoparticle suspension N;

[0016] Step (4) adding an initiator to the anti-inflammatory substance nanoparticle suspension N to obtain an initiator solution G, and then adding the modified biomacromolecule to the initiator solution G to obtain a hydrogel precursor solution H;

[0017] Step (5) spreading the hydrogel precursor solution H to the inner layer of the polymer fiber layer of the electrostatically deposited growth factor nanoparticles obtained in step (2), and cross-linking by ultraviolet light to obtain the patch material for controllable delivery of anti-inflammatory substances.

[0018] In the method for preparing the above anti-inflammatory patch material, in step (1):

[0019] The solvent in the polymer solution A is selected from at least one of hexafluoroisopropanol, trifluoroethanol, chloroform, methanol, dichloromethane, and N,N'-dimethylformamide; the mass percentage concentration of the polymer solution A is 5 to 25%, preferably 8 to 15%;

[0020] The electrospinning comprises: performing uniaxial electrospinning on a polymer solution A, using a roller or a U-shaped groove as a receiver, the spinning solution flow rate is 0.1-3 mL / h, the voltage is 10-20 kV, and the receiving distance is 10-20 cm; preferably, when the electrospinning uses a roller as a receiver, first spinning for 2-10 hours with a high-speed rotating roller as a receiver, and then spinning for 2-10 hours by reducing the roller speed; or, when the electrospinning uses a U-shaped groove as a receiver, spinning for 2-10 hours with the U-shaped groove as a receiver, and then peeling the collected fiber membrane from the U-shaped groove, removing the U-shaped groove, and placing the obtained fiber membrane on tin foil as a receiver for spinning for 2-10 hours.

[0021] In the method for preparing the above anti-inflammatory patch material, in step (2):

[0022] The solvent of the growth factor solution B is selected from at least one of phosphate buffered saline (PBS), water, ethanol, polyvinyl alcohol, polyacrylamide, and polyacrylic acid; the concentration of the growth factor solution B is 0.1 μg / mL to 5 mg / mL, preferably 1 μg / mL to 1 mg / mL;

[0023] The solvent in the bioactive substance solution C is selected from at least one of hydrochloric acid, acetic acid, ethyl acetate, glycerol, trifluoroethanol, and hexafluoroisopropanol; the concentration of the bioactive substance solution C is 1 to 50 mg / mL, preferably 10 to 30 mg / mL;

[0024] The coaxial electrostatic spraying comprises: using a mask mode to perform electrostatic spraying of gradient concentration, regulating the electrostatic spraying time at different positions on the fiber surface by moving the mask, and depositing bioactive material particles in a manner that the particle density increases gradiently along the fiber orderly arrangement direction. Specifically, using a mask mode to deposit bioactive material particles in a manner that the particle density increases gradiently along the fiber orderly arrangement direction, injecting a bioactive material solution C into a shell layer syringe, and injecting a growth factor solution B into a core layer syringe, the inner layer of the polymer fiber layer obtained in step (1) is used as a receiver, the flow rate of the shell layer electrospraying solution is 0.5 to 3 mL / h, the flow rate of the core layer electrospraying solution is 0.2 to 1 mL / h, the voltage is 10 to 20 kV, the receiving distance is 10 to 20 cm, and the electrostatic spraying time is 1 to 60 min; the density of the growth factor nanoparticles in the obtained polymer fiber membrane increases gradiently along the fiber arrangement direction;

[0025] The polymer fiber material obtained after electrostatic spraying needs to be freed of solvent, which can be removed by a common solvent removal method or left to evaporate, such as placing it in a fume hood at room temperature for 2-7 days. After the solvent is removed, it is packaged and disinfected.

[0026] In the method for preparing the above anti-inflammatory patch material, in step (3):

[0027] The solvent of the anti-inflammatory substance solution D is selected from at least one of phosphate buffered saline (PBS), water, chloroform, glycerol, trifluoroethanol, and hexafluoroisopropanol; the concentration of the anti-inflammatory substance solution D is 1 μg / mL to 5 mg / mL, preferably 0.1 to 2 mg / mL;

[0028] The solvent of the cationic polymer solution E is at least one of phosphate buffered saline, water, ethanol, polyvinyl alcohol, polyacrylamide, and polyacrylic acid; the concentration of the cationic polymer solution E is 1 μg / mL to 5 mg / mL, preferably 0.05 to 2 mg / mL;

[0029] The solvent of the polyphenol compound solution F is at least one of phosphate buffered saline, water, chloroform, glycerol, trifluoroethanol, and hexafluoroisopropanol; the concentration of the polyphenol compound solution F is 1 μg / mL to 5 mg / mL, preferably 0.05 to 2 mg / mL;

[0030] In the suspension M, the volume ratio of the anti-inflammatory substance solution D to the cationic polymer solution E is 1:(0.1-10), preferably 1:(0.5-3); in the suspension N, the volume ratio of the polyphenol compound solution F to the suspension M is 1:(0.1-10), preferably 1:(0.5-3).

[0031] In the method for preparing the above anti-inflammatory patch material, in step (4):

[0032] The initiator is selected from at least one of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959), phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), and ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L); the mass percentage of the initiator in the initiator solution G is 0.1 to 0.5%, preferably 0.15 to 0.3%;

[0033] The mass percentage of the modified biomacromolecules in the hydrogel precursor solution H is 5 to 15%, preferably 8 to 12%;

[0034] In step (4), the initiator is added to the anti-inflammatory substance nanoparticle suspension N, and the mixture is kept in the dark at 37°C, and the initiator solution G is obtained after sufficient shaking and mixing. When preparing the hydrogel precursor solution H, the initiator solution G is first placed in a constant temperature water bath in the dark and heated to 37°C, and then the modified biomacromolecule is added to the initiator solution G, and the mixture is kept in the dark and sufficiently shaking and mixing at 37°C to obtain the hydrogel precursor solution H.

[0035] In step (5) of the preparation method of the above-mentioned anti-inflammatory patch material, the hydrogel precursor solution is cured by photo-crosslinking, and the operation steps include: first, heating the hydrogel precursor solution H to 37°C in a constant temperature water bath in the dark, then adding the hydrogel precursor solution H into a syringe and rapidly spreading it through a 0.22 μm filter into the polymer fiber layer of electrostatically deposited growth factor nanoparticles, and curing the fibers after the hydrogel is spread under light, and the photo-curing time is 4 to 30 seconds.

[0036] The third purpose of the present invention is to provide the above-mentioned patch material for controllable delivery of anti-inflammatory substances or the patch material for controllable delivery of anti-inflammatory substances obtained by the above-mentioned preparation method, and its application in spinal cord contusion.

[0037] Furthermore, when the patch material of the present invention that can controllably deliver anti-inflammatory substances is used as a spinal cord contusion repair material, the controlled delivery of nanoparticles containing anti-inflammatory substances is achieved by regulating the degradation rate of the hydrogel, which can inhibit the severe inflammatory response in the early stage of the injury. Among them, the polyphenol compounds in the outer layer of the nanoparticles can achieve their long-term residence in the lesion site, avoiding problems such as low efficiency caused by the flow of cerebrospinal fluid. In addition, while regulating the inflammatory response, by constructing nanofibers with a unidirectional ordered topological structure, combining the gradient density of surfactant particles, and introducing pro-repair growth factors, cell migration and nerve axon extension are promoted. The patch material that can controllably deliver anti-inflammatory substances can improve the microenvironment of spinal cord contusion, create conditions for the regulation of inflammatory response and subsequent injury repair, and after the spinal cord contusion repair process is completed, the patch can be degraded and metabolized by the body.

[0038] The present invention combines a hydrogel with adjustable degradation rate as a carrier of drug-loaded nanoparticles and an electrospun nanofiber scaffold similar to the extracellular matrix structure to form an ideal design for controllable release of anti-inflammatory nanoparticles. The presence of the hydrogel can achieve in situ controllable delivery of drug-loaded nanoparticles and improve the action efficiency of the nanoparticles. The electrospun nanofibers with adjustable topological structure can stabilize the morphology of the hydrogel and guide and promote the subsequent repair of spinal cord contusion after the hydrogel is degraded.

[0039] The present invention can achieve the following beneficial effects:

[0040] 1. The nanoparticle drug delivery system used in the present invention avoids direct exposure of the drug in the body, prolongs the half-life of the drug, and the presence of polyphenols on the surface of the nanoparticles enables the nanoparticles to be retained in the damaged area for a long time;

[0041] 2. The present invention uses hydrogels with adjustable degradation rates to wrap drug-loaded nanoparticles, which can achieve in-situ controllable delivery of drug-loaded nanoparticles and improve the efficiency of the nanoparticles. The controllable delivery system of anti-inflammatory substances used in the present invention can effectively inhibit the severe inflammatory response in the early stage of spinal cord contusion, so that the inflammatory microenvironment in the early stage of spinal cord contusion is regulated in a long-term and stable manner, and provide a suitable microenvironment for subsequent axon regeneration.

[0042] 3. The present invention adopts an electrospun nanofiber and hydrogel rigid-flexible composite design, which significantly improves the mechanical properties of the hydrogel. The presence of nanofibers is beneficial to stabilizing the morphology of the hydrogel. The nanofibers prepared by electrospinning can imitate the function of the extracellular matrix (ECM) as much as possible, and have the ability to controllably release a variety of growth factors. In addition, due to the gradient density signal of the growth factor nanoparticles deposited in the inner layer of the nanofibers and the unidirectional orderly arranged fiber structure, it can promote the regeneration and migration of axons in the damaged area for a long time after the hydrogel is degraded.

[0043] 4. The randomly arranged fibers of the outer layer of the degradable aliphatic polyester fiber of the present invention provide sufficient elasticity and toughness to meet the needs of spinal movement during and after surgery;

[0044] 5. The anti-inflammatory patch material of the present invention has excellent biocompatibility and degradation performance, and can realize the controllable delivery of anti-inflammatory substances to regulate the microenvironment after spinal cord contusion, promote the subsequent repair process and improve the repair effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a scanning electron microscope image of the double-layer polymer fiber layer obtained in Example 1. It can be seen that the double-layer polymer fiber layer has an inner layer of fibers arranged in an orderly unidirectional manner and an outer layer of fibers arranged randomly, indicating that Example 1 successfully prepared a polymer fiber with a double-layer structure.

[0046] Figure 2 This is a scanning electron microscope image of the hydrogel layer in the patch material for controllable delivery of anti-inflammatory substances obtained in Example 1. The porous structure in the image shows the morphology of the hydrogel layer, indicating that Example 1 successfully prepared a polymer fiber and hydrogel rigid-flexible composite patch.

[0047] Figure 3 The water contact angles of the polymer fiber with gradient density growth factor particles deposited on the inner surface obtained in Example 1 and the polymer fiber with uniform density growth factor particles deposited on the inner surface obtained in Comparative Example 1.

[0048] Figure 4 The strain curve of the polymer fiber layer with a double-layer structure obtained in Example 1 before and after PBS infiltration, the abscissa is the strain, and the ordinate is the stress that changes with the strain. Figure 4 It can be seen that the mechanical properties of the polymer fiber layer are maintained at a relatively strong level before and after PBS infiltration. Since the polymer fiber layer is the main part that provides the mechanical properties of the patch material of the present invention, the patch material obtained by using the double-layer polymer fiber layer provided by the present invention can also maintain excellent mechanical properties and provide sufficient mechanical strength during and after surgery.

[0049] Figure 5 : is the particle size distribution of the anti-inflammatory substance nanoparticle suspension N obtained in Example 1, the abscissa is the size of the nanoparticles, and the ordinate is the proportion of nanoparticles of the corresponding size. Figure 5 It shows that the anti-inflammatory substance nanoparticles obtained in Example 1 are very small in size and have a relatively uniform particle size distribution, indicating that the anti-inflammatory substance nanoparticles in Example 1 can more effectively play an anti-inflammatory role in the damaged area, regulate the damaged microenvironment, and promote repair. DETAILED DESCRIPTION

[0050] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0051] The test instruments and test conditions used in the examples are as follows:

[0052] Electrospinning equipment: Model: TEADFS-103, Beijing Xinrui Baina Technology Co., Ltd.; (roller as receiver)

[0053] Electrospinning equipment: Model: NANO 01, MECC Co., Ltd., Japan; (U-shaped groove as receiver)

[0054] Electrostatic spray equipment: Model: NANO 01, Japan MECC Co., Ltd.

[0055] Universal material testing machine: Model: CMT4104, Shenzhen Sansi Company;

[0056] Nanoparticle size analyzer: Model: C-W10X10XB22, Shanghai Beimi Biotechnology Co., Ltd.

[0057] Test method for tensile properties: Use universal material testing machine CMT4104 to conduct tensile tests on polymer fiber membranes to test the mechanical properties of the materials. First, cut the material into a dumbbell shape, use a digital micrometer table thickness gauge to measure the thickness of the sample at different positions, and take the average of 3 measurement results as the sample thickness. Make 3 parallel samples for each sample to ensure the accuracy of the results, clamp the sample vertically on the fixture of the universal material testing machine, set the tensile speed to 50mm / min, and the maximum tensile length to 200mm for tensile testing.

[0058] The raw materials and sources used in the examples are as follows:

[0059] The degradable aliphatic polyester raw materials used in the examples were purchased from Sigma Reagent Company, organic solvents were purchased from Aladdin Company, and growth factors were purchased from Thermo Fisher Scientific Company. Modified biomacromolecules and initiators were purchased from EFL Company, anti-inflammatory substances and cationic polymers were purchased from Yuanye Company, and polyphenol compounds were purchased from Macklin Company.

[0060] Unless otherwise specified, other raw materials used in the embodiments and comparative examples are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation method disclosed in the prior art.

[0061] Embodiment 1:

[0062] Step (1) preparing a polylactic acid-glycolic acid copolymer (PLGA) solution in a volume ratio of dichloromethane:N,N-dimethylformamide=4:1, and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 10%; using solution A for uniaxial electrospinning, the flow rate of solution A is 1 mL / h, the voltage is 16 kV, the receiving distance is 15 cm, and a high-speed rotating roller is used as a receiver. The spinning is performed for 5 hours to obtain unidirectional orderly arranged fibers, and then the roller speed is gradually reduced, and the randomly arranged fibers are continuously collected for 5 hours to obtain a double-layer polymer fiber layer; the polymer fibers are placed in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;

[0063] Step (2) dissolving neurotrophic factor-3 in PBS and mixing well to obtain a growth factor solution B with a concentration of 100 μg / mL; dissolving collagen in an acetic acid aqueous solution with a volume fraction of 70%, mixing well to obtain a bioactive substance solution C with a concentration of 20 mg / mL; replacing the electrospray liquid with growth factor solution B and bioactive substance solution C, replacing the uniaxial spinning needle with a coaxial needle, injecting the growth factor solution B into the core layer syringe, and injecting the bioactive substance solution C into the shell layer syringe; the inner layer of the polymer fiber obtained in step (1) is used as a receiver, and coaxial electrostatic spraying is performed, and a mask strategy is adopted to deposit bioactive substance particles with a particle density gradient increasing along the orderly arrangement direction of the fiber, the flow rate of the growth factor solution B is 0.5 mL / h, the flow rate of the bioactive substance solution C is 1.5 mL / h, the voltage is 20 kV, and the electrostatic spraying is performed for 30 minutes to deposit the growth factor particles on the inner surface of the polymer fiber with a gradient density;

[0064] Step (3) adding catalase and superoxide dismutase to water, mixing them thoroughly to obtain an anti-inflammatory substance solution D with a concentration of 1 mg / mL; adding polylysine to water, mixing them thoroughly to obtain a cationic polymer solution E with a concentration of 50 μg / mL; mixing the two solutions in a volume ratio of 1:1, and magnetically stirring at room temperature for 30 minutes to obtain a suspension M; adding tannic acid to water, mixing them thoroughly to obtain a polyphenol compound solution F with a concentration of 0.1 mg / mL; mixing solution F with suspension M in a volume ratio of 1:2, and magnetically stirring at room temperature for 30 minutes to obtain an anti-inflammatory substance nanoparticle suspension N;

[0065] Step (4) adding LAP initiator to the anti-inflammatory substance nanoparticle suspension N obtained in step (3), shaking and mixing at 37° C. in the dark, to obtain an initiator solution G with a mass fraction of 0.25%; adding methacrylated gelatin to the initiator solution G, shaking and mixing at 37° C. in the dark, to obtain a hydrogel precursor solution H with a mass fraction of 10%;

[0066] Step (5) first heats the hydrogel precursor solution H obtained in step (4) to 37° C. in a constant temperature water bath in the dark, then adds the hydrogel precursor solution H into a syringe and quickly spreads it through a 0.22 μm filter to the polymer fiber layer with gradient density deposited collagen particles on the inner surface obtained in step (2), and cures the fibers after spreading the hydrogel under 405 nm blue light for 8 seconds to obtain a spinal cord contusion patch material with controllable delivery of anti-inflammatory substances.

[0067] Embodiment 2:

[0068] Step (1) adding polycaprolactone to N,N-dimethylformamide, and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 10%; performing uniaxial electrospinning with the solution A, the flow rate of the solution A being 1 mL / h, the voltage being 16 kV, the receiving distance being 15 cm, and a high-speed rotating roller being used as a receiver, spinning for 5 hours to obtain unidirectional orderly arranged fibers, then gradually reducing the roller speed, and continuing to collect randomly arranged fibers for 5 hours to obtain a double-layer polymer fiber layer; placing the polymer fibers in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;

[0069] Step (2) dissolving brain-derived neurotrophic factor in PBS and mixing well to obtain a brain-derived neurotrophic factor solution B with a concentration of 100 μg / mL; dissolving collagen in an acetic acid aqueous solution with a volume fraction of 70%, mixing well to obtain a bioactive substance solution C with a concentration of 20 mg / mL; replacing the electrospray liquid with brain-derived neurotrophic factor solution B and bioactive substance solution C, replacing the uniaxial spinning needle with a coaxial needle, injecting brain-derived neurotrophic factor solution B into the nuclear layer syringe, and injecting bioactive substance solution C into the shell layer syringe; the inner layer of the polymer fiber obtained in step (1) is used as a receiver, and coaxial electrostatic spraying is performed, and a mask strategy is adopted to deposit bioactive substance particles with a particle density gradient increasing along the orderly arrangement direction of the fiber, the flow rate of brain-derived neurotrophic factor B is 0.5 mL / h, the flow rate of bioactive substance solution C is 1.5 mL / h, the voltage is 20 kV, and the electrostatic spraying is performed for 30 minutes to deposit growth factor particles with gradient density on the inner surface of the polymer fiber;

[0070] Step (3) adding curcumin and resveratrol to water and mixing them thoroughly to obtain an anti-inflammatory substance solution D with a concentration of 1 mg / mL; adding polylysine to water and mixing them thoroughly to obtain a cationic polymer solution E with a concentration of 50 μg / mL; mixing the two solutions in a volume ratio of 1:1, and magnetically stirring at room temperature for 30 minutes to obtain a suspension M; adding tannic acid to water and mixing them thoroughly to obtain a polyphenol compound solution F with a concentration of 0.1 mg / mL; mixing solution F and suspension M in a volume ratio of 1:2, and magnetically stirring at room temperature for 30 minutes to obtain an anti-inflammatory substance nanoparticle suspension N;

[0071] Step (4) adding I2929 initiator to the anti-inflammatory substance nanoparticle suspension N obtained in step (3), shaking and mixing at 37° C. in the dark, to obtain an initiator solution G with a mass fraction of 0.25%; adding methacrylated gelatin to the initiator solution G, shaking and mixing at 37° C. in the dark, to obtain a hydrogel precursor solution H with a mass fraction of 10%;

[0072] Step (5) first heats the hydrogel precursor solution H obtained in step (4) to 37° C. in a constant temperature water bath in the dark, then adds the hydrogel precursor solution H into a syringe and quickly spreads it through a 0.22 μm filter to the polymer fiber layer with gradient density deposited collagen particles on the inner surface obtained in step (2), and cures the fibers after spreading the hydrogel under 405 nm blue light for 8 seconds to obtain a spinal cord contusion patch material with controllable delivery of anti-inflammatory substances.

[0073] Example 3

[0074] Step (1) preparing a polylactic acid-glycolic acid copolymer (PLGA) solution in a volume ratio of dichloromethane:N,N-dimethylformamide=4:1, and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 12%; using solution A for uniaxial electrospinning, the flow rate of solution A is 0.8 mL / h, the voltage is 15 kV, the receiving distance is 15 cm, and the U-shaped groove is used as a receiver. The spinning is performed for 6 hours to obtain a unidirectional ordered fiber membrane, and then the U-shaped groove is removed, and the unidirectional ordered fiber membrane obtained is used as a collector to collect randomly arranged fibers, and the collection is performed for 6 hours to obtain a double-layer polymer fiber layer; the polymer fiber is placed in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;

[0075] Step (2) dissolving neurotrophic factor-3 in PBS and mixing well to obtain a growth factor solution B with a concentration of 150 μg / mL; dissolving collagen in an acetic acid aqueous solution with a volume fraction of 70%, mixing well to obtain a bioactive substance solution C with a concentration of 20 mg / mL; replacing the electrospray liquid with growth factor solution B and bioactive substance solution C, replacing the uniaxial spinning needle with a coaxial needle, injecting the growth factor solution B into the core layer syringe, and injecting the bioactive substance solution C into the shell layer syringe; the inner layer of the polymer fiber obtained in step (1) is used as a receiver, and coaxial electrostatic spraying is performed, and a mask strategy is adopted to deposit bioactive substance particles with a particle density gradient increasing along the orderly arrangement direction of the fiber, the flow rate of the growth factor solution B is 0.3 mL / h, the flow rate of the bioactive substance solution C is 1 mL / h, the voltage is 18 kV, and the electrostatic spraying is performed for 15 minutes to deposit the growth factor particles on the inner surface of the polymer fiber with a gradient density;

[0076] Step (3) adding IL-10 and IL-4 to PBS and mixing them thoroughly to obtain an anti-inflammatory substance solution D with a concentration of 500 μg / mL; adding polylysine to water and mixing them thoroughly to obtain a cationic polymer solution E with a concentration of 100 μg / mL; mixing the two solutions at a volume ratio of 1:0.5, and magnetically stirring at room temperature for 30 minutes to obtain a suspension M; adding tannic acid to water and mixing them thoroughly to obtain a polyphenol compound solution F with a concentration of 80 μg / mL; mixing solution F and suspension M at a volume ratio of 1:1, and magnetically stirring at room temperature for 30 minutes to obtain an anti-inflammatory substance nanoparticle suspension N;

[0077] Step (4) adding Irgacure 2959 initiator to the anti-inflammatory substance nanoparticle suspension N obtained in step (3), shaking and mixing at 37° C. in the dark, to obtain an initiator solution G with a mass fraction of 0.25%; adding methacrylylated silk fibroin to the initiator solution G, shaking and mixing at 37° C. in the dark, to obtain a hydrogel precursor solution H with a mass fraction of 8%;

[0078] Step (5) first heats the hydrogel precursor solution H obtained in step (4) to 37° C. in a constant temperature water bath in the dark, then adds the hydrogel precursor solution H into a syringe and quickly spreads it through a 0.22 μm filter to the polymer fiber layer with gradient density deposited collagen particles on the inner surface obtained in step (2), and cures the fibers after spreading the hydrogel under 365 nm ultraviolet light for 10 seconds to obtain a spinal cord contusion patch material with controllable delivery of anti-inflammatory substances.

[0079] Comparative Example 1:

[0080] Step (1) preparing a PLGA solution in a volume ratio of dichloromethane:N,N-dimethylformamide=4:1, and magnetically stirring at room temperature for 24 hours to obtain a polymer solution A with a mass concentration of 10%; using solution A for uniaxial electrospinning, the flow rate of solution A is 1 mL / h, the voltage is 16 kV, the receiving distance is 15 cm, and a high-speed rotating roller is used as a receiver. The spinning is performed for 5 hours to obtain unidirectional orderly arranged fibers, and then the roller speed is gradually reduced, and the randomly arranged fibers are continuously collected for 5 hours to obtain a double-layer polymer fiber layer; the polymer fibers are placed in a fume hood at room temperature for 3 days to allow the residual solvent to fully evaporate;

[0081] Step (2) dissolving neurotrophic factor-3 in PBS and mixing well to obtain neurotrophic factor-3 solution B with a concentration of 100 μg / mL; dissolving collagen in acetic acid aqueous solution with a volume fraction of 70%, mixing well to obtain bioactive substance solution C with a concentration of 20 mg / mL; replacing the electrospray liquid with brain-derived neurotrophic factor solution B and bioactive substance solution C, replacing the uniaxial spinning needle with a coaxial needle, injecting neurotrophic factor-3 solution B into the core layer syringe, and injecting bioactive substance solution C into the shell layer syringe; the inner layer of the polymer fiber obtained in step (1) is used as a receiver, and coaxial electrostatic spraying is performed to uniformly deposit bioactive substance particles, the flow rate of neurotrophic factor-3 solution B is 0.5 mL / h, the flow rate of bioactive substance solution C is 1.5 mL / h, the voltage is 20 kV, and the electrostatic spraying is performed for 30 minutes to uniformly deposit growth factor particles on the inner surface of the polymer fiber.

[0082] The polymer fiber membrane prepared in this comparative example is the one corresponding to Example 1, with collagen particles deposited at a uniform density on the inner surface. Figure 3 The water contact angles of the polymer fiber with gradient density deposited growth factor particles on the inner surface obtained in Example 1 and the polymer fiber with uniform density deposited growth factor particles on the inner surface obtained in Comparative Example 1 indicate that the gradient density deposition of growth factor particles in Example 1 can significantly improve the hydrophilicity of the fiber, which is beneficial to cell adhesion.

Claims

1. A patch material for controllably delivering anti-inflammatory substances, comprising a polymer fiber layer and a hydrogel layer, wherein the polymer fiber layer is a double-layer polymer fiber layer with growth factor nanoparticles deposited on the surface, and the hydrogel layer is a modified biomacromolecule hydrogel containing anti-inflammatory substance nanoparticles.

2. The patch material according to claim 1, characterized in that: The thickness of the polymer fiber layer is 50 to 800 μm, preferably 100 to 500 μm; and / or, The thickness of the hydrogel layer is 50 to 800 μm, preferably 100 to 500 μm; and / or, The inner layer of the polymer fiber layer is a unidirectional orderly arranged polymer fiber layer with growth factor nanoparticles deposited on the surface, and the outer layer is a randomly arranged polymer fiber layer; and / or, The growth factor nanoparticles are of a core-shell structure, wherein the shell layer is a biologically active substance and the core layer is a growth factor; and / or, The particle size of the growth factor nanoparticles is 30 to 200 nm, preferably 50 to 150 nm; and / or, The anti-inflammatory substance nanoparticles comprise a three-layer structure, wherein the inner layer is the anti-inflammatory substance, the middle layer is the cationic polymer, and the outer layer is the polyphenol compound; and / or, The particle size of the anti-inflammatory substance nanoparticles is 30 to 200 nm, preferably 50 to 100 nm; and / or, The modified biomacromolecule is an acrylated biomacromolecule.

3. The patch material according to claim 2, characterized in that: The polymer in the polymer fiber layer is selected from degradable aliphatic polyesters, preferably at least one selected from polylactic acid, polycaprolactone, polylactic acid-glycolic acid copolymer, polylactic acid-glycolic acid-caprolactone copolymer; and / or, The bioactive substance is selected from at least one of protein compounds, preferably at least one of collagen, laminin, fibronectin, and collagen; and / or, The growth factor is selected from at least one of vascular endothelial growth factor, fibroblast growth factor, epidermal growth factor, brain-derived neurotrophic factor, neurotrophin-3, glial cell-derived neurotrophic factor, ciliary neurotrophic factor, and nerve growth factor; and / or, The anti-inflammatory substance is selected from at least one of catalase, superoxide dismutase, interleukin, and reducing molecules; and / or, The cationic polymer is selected from at least one of polyarginine, polylysine, gelatin, polyhistidine, polyethyleneimine, polyacrylamide and polyacrylamine; and / or, The polyphenolic compound is selected from at least one of flavonoids, tannins, phenolic acids and anthocyanins; and / or, The modified biomacromolecule is selected from at least one of methacrylylated gelatin, methacrylylated hyaluronic acid, methacrylylated silk fibroin, methacrylylated chitosan, and methacrylylated sodium alginate.

4. A method for preparing a patch material for controllably delivering an anti-inflammatory substance according to any one of claims 1 to 3, comprising: The polymer solution is electrospun to obtain a double-layer nanofiber membrane with an inner layer of uniaxially ordered nanofibers and an outer layer of randomly arranged nanofibers, and growth factor nanoparticles are then deposited on the surface of the inner fiber layer by electrostatic spraying. Subsequently, a suspension containing anti-inflammatory nanoparticles is mixed with a modified biomacromolecule solution and a cross-linking agent, spread onto the surface of the inner fiber layer and cross-linked under ultraviolet light to obtain the patch material for controllable delivery of anti-inflammatory substances.

5. The preparation method according to claim 4, characterized in that: The preparation method specifically comprises the following steps: Step (1) electrospinning the polymer solution A to prepare a double-layer polymer fiber layer; Step (2) using coaxial electrostatic spraying to spray the growth factor solution B and the bioactive substance solution C onto the inner surface of the double-layer polymer fiber layer to obtain a polymer fiber layer with electrostatically deposited growth factor nanoparticles; Step (3) mixing the anti-inflammatory substance solution D with the cationic polymer solution E to obtain a suspension M, and then adding the polyphenol compound solution F to the suspension M to obtain an anti-inflammatory substance nanoparticle suspension N; Step (4) adding an initiator to the anti-inflammatory substance nanoparticle suspension N to obtain an initiator solution G, and then adding the modified biomacromolecule to the initiator solution G to obtain a hydrogel precursor solution H; Step (5) spreading the hydrogel precursor solution H to the inner layer of the polymer fiber layer of the electrostatically deposited growth factor nanoparticles obtained in step (2), and cross-linking by ultraviolet light to obtain the patch material for controllable delivery of anti-inflammatory substances.

6. The preparation method according to claim 5, characterized in that: In the step (1): The solvent in the polymer solution A is selected from at least one of hexafluoroisopropanol, trifluoroethanol, chloroform, methanol, dichloromethane and N,N'-dimethylformamide; and / or, The mass percentage concentration of the polymer solution A is 5 to 25%, preferably 8 to 15%; and / or, The electrospinning comprises: performing uniaxial electrospinning on a polymer solution A, using a roller or a U-shaped groove as a receiver, the spinning solution flow rate is 0.1-3 mL / h, the voltage is 10-20 kV, and the receiving distance is 10-20 cm; preferably, when the electrospinning uses a roller as a receiver, first spinning for 2-10 hours with a high-speed rotating roller as a receiver, and then spinning for 2-10 hours by reducing the roller speed; or, when the electrospinning uses a U-shaped groove as a receiver, spinning for 2-10 hours with the U-shaped groove as a receiver, and then peeling the collected fiber membrane from the U-shaped groove, removing the U-shaped groove, and placing the obtained fiber membrane on tin foil as a receiver for spinning for 2-10 hours.

7. The preparation method according to claim 5, characterized in that: In the step (2): The solvent of the growth factor solution B is selected from at least one of phosphate buffered saline, water, ethanol, polyvinyl alcohol, polyacrylamide, and polyacrylic acid; and / or, The concentration of the growth factor solution B is 0.1 μg / mL to 5 mg / mL, preferably 1 μg / mL to 1 mg / mL; and / or, The solvent in the bioactive substance solution C is selected from at least one of hydrochloric acid, acetic acid, ethyl acetate, glycerol, trifluoroethanol, and hexafluoroisopropanol; and / or, The concentration of the bioactive substance solution C is 1 to 50 mg / mL, preferably 10 to 30 mg / mL; and / or, The coaxial electrostatic spraying comprises: using a mask pattern to deposit bioactive substance particles in a gradient increasing manner along the direction of orderly fiber arrangement, injecting a bioactive substance solution C into a shell layer syringe, injecting a growth factor solution B into a core layer syringe, the inner layer of the polymer fiber layer obtained in step (1) is used as a receiver, the flow rate of the shell layer electrospraying solution is 0.5 to 3 mL / h, the flow rate of the core layer electrospraying solution is 0.2 to 1 mL / h, the voltage is 10 to 20 kV, the receiving distance is 10 to 20 cm, and the electrostatic spraying time is 1 to 60 minutes.

8. The preparation method according to claim 5, characterized in that: In the step (3): The solvent of the anti-inflammatory substance solution D is selected from at least one of phosphate buffered saline, water, chloroform, glycerol, trifluoroethanol, and hexafluoroisopropanol; and / or, The concentration of the anti-inflammatory substance solution D is 1 μg / mL to 5 mg / mL, preferably 0.1 to 2 mg / mL; and / or, The solvent of the cationic polymer solution E is at least one of phosphate buffered saline, water, ethanol, polyvinyl alcohol, polyacrylamide, and polyacrylic acid; and / or, The concentration of the cationic polymer solution E is 1 μg / mL to 5 mg / mL, preferably 0.05 to 2 mg / mL; and / or, The solvent of the polyphenol compound solution F is at least one of phosphate buffered saline, water, chloroform, glycerol, trifluoroethanol, and hexafluoroisopropanol; and / or, The concentration of the polyphenol compound solution F is 1 μg / mL to 5 mg / mL, preferably 0.05 to 2 mg / mL; and / or, In the suspension M, the volume ratio of the anti-inflammatory substance solution D to the cationic polymer solution E is 1:(0.1-10), preferably 1:(0.5-3); and / or, In the suspension N, the volume ratio of the polyphenol compound solution F to the suspension M is 1:(0.1-10), preferably 1:(0.5-3).

9. The preparation method according to claim 5, characterized in that: In the step (4): The initiator is selected from at least one of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, and ethyl 2,4,6-trimethylbenzoylphenylphosphonate; and / or, The mass percentage of the initiator in the initiator solution G is 0.1 to 0.5%, preferably 0.15 to 0.3%; and / or, The mass percentage of the modified biomacromolecules in the hydrogel precursor solution H is 5 to 15%, preferably 8 to 12%.

10. Use of a patch material capable of controllably delivering anti-inflammatory substances as claimed in any one of claims 1 to 3 or a patch material capable of controllably delivering anti-inflammatory substances obtained by the preparation method as claimed in any one of claims 4 to 9 in spinal cord contusion.